2003
DOI: 10.1007/s00122-003-1517-4
|View full text |Cite
|
Sign up to set email alerts
|

EST-derived microsatellites from Actinidia species and their potential for mapping

Abstract: To increase the speed and reduce the cost of constructing a genetic map of Actinidia species (kiwifruit), for use in both breeding and functional genomics programmes, we sampled microsatellites from expressed sequence tags (ESTs) to evaluate their frequency of occurrence and level of polymorphism. Perfect dinucleotide repeats were the microsatellites selected, and these were found to be numerous in both the 5' and 3' ends of the genes represented. The microsatellites were of various lengths, the majority being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
48
0
7

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(71 citation statements)
references
References 24 publications
16
48
0
7
Order By: Relevance
“…In Mangifera indica and Nelumbo nucifera, tetranucleotides and pentanucleotides were completely absent, whereas in Tinospora cordifolia, hexanucleotide was completely absent. The dinucleotide repeats (DNRs) are more frequent than the trinucleotide repeats (TNRs) in ESTs of Ananas comosus, Carica papaya, Catharanthus roseus, Jatropha curcas, Morus indica, and Nelumbo nucifera, similar to the previous reports in Actinidia (Fraser et al, 2004), Camellia (Sahu et al, 2012), and Picea species (Rungis et al, 2004). But the frequencies of TNRs were found to be more than DNRs in Citrus aurantium, Cynodon dactylon, Dioscorea alata, Mangifera indica, and Tinospora cordifolia, similar to most previous studies (Cordeiro et al, 2001;Kantety et al, 2002;Varshney et al, 2002;Thiel et al, 2003;Nicot et al, 2004).…”
Section: Discussionsupporting
confidence: 86%
“…In Mangifera indica and Nelumbo nucifera, tetranucleotides and pentanucleotides were completely absent, whereas in Tinospora cordifolia, hexanucleotide was completely absent. The dinucleotide repeats (DNRs) are more frequent than the trinucleotide repeats (TNRs) in ESTs of Ananas comosus, Carica papaya, Catharanthus roseus, Jatropha curcas, Morus indica, and Nelumbo nucifera, similar to the previous reports in Actinidia (Fraser et al, 2004), Camellia (Sahu et al, 2012), and Picea species (Rungis et al, 2004). But the frequencies of TNRs were found to be more than DNRs in Citrus aurantium, Cynodon dactylon, Dioscorea alata, Mangifera indica, and Tinospora cordifolia, similar to most previous studies (Cordeiro et al, 2001;Kantety et al, 2002;Varshney et al, 2002;Thiel et al, 2003;Nicot et al, 2004).…”
Section: Discussionsupporting
confidence: 86%
“…As exactly as most crops (Fraser et al, 2004;Jung et al, 2005;Aggarwal et al, 2007), Feng et al (2009) reported that DNRs were the main repeat motif, and AG / TC were the predominant DNRs; In this study, 61 sequences were recovered from 5 loci, of which 44 sequences belonged to AG / TC repeats.…”
Section: Detection Of Loci Variationsupporting
confidence: 62%
“…In fact, an estimated 2-5% of all plant-derived ESTs are thought to harbor SSRs (Kantety et al, 2002), although the actual frequency of SSR-bearing ESTs in any particular analysis is highly dependent on the search parameters (see below). Moreover, a large fraction of EST-SSRs (on the order of 80-90%) are typically found to be polymorphic (Bandopadhyay et al, 2004;Fraser et al, 2004;Pashley et al, 2006). Taking into account typical marker development attrition rates, it therefore seems likely that EST databases containing as few as 1000 sequences could provide enough markers to facilitate population genetic analyses.…”
Section: Est Resources and Ssr Frequenciesmentioning
confidence: 99%